Mycobacterium avium complex (MAC) isolated from AIDS patients and the criteria required for its implication in disease - Hadad, David Jamil; Palhares, Maria Cecília de Almeida; Placco, Anna Luiza Nunes; Domingues, Carmem Silvia Bruniera; Castelo Filho, Adauto; Ferrazoli, Lucilaine; Ueki, Sueli Yoko Mizuka; Telles, Maria Alice da Silva; Martins, Maria Conceição; Palaci, Moisés (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
Before the AIDS pandemia, the Mycobacterium avium complex (MAC) was responsible in most cases for the pneumopathies that attack patients with basic chronic pulmonary diseases such as emphysema and chronic bronchitis36. In 1981, with the advent of the acquired immunodeficiency syndrome (AIDS), MAC started to represent one of the most frequent bacterial diseases among AIDS patients, with the disseminated form of the disease being the major clinical manifestation of the infection8. Between January 1989 and February 1991, the Section of Mycobacteria of the Adolfo Lutz Institute, São Paulo, isolated MAC from 103 patients by culturing different sterile and no-sterile processed specimens collected from 2304 patients seen at the AIDS Reference and Training Center and/or Emilio Ribas Infectology Institute. Disseminated disease was diagnosed in 29 of those patients on the basis of MAC isolation from blood and/or bone marrow aspirate. The other 74 patients were divided into categories highly (5), moderately (26) and little suggestive of disease (43) according to the criteria of DAVIDSON (1989)10. The various criteria for MAC isolation from sterile and non-sterile specimens are discussed.